1987
DOI: 10.1128/aac.31.11.1761
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to TEM-1 plasmid-mediated beta-lactamase

Abstract: At least 28 plasmid-mediated j-lactamases have been described in gram-negative bacteria. To assess the relationship among these enzymes, we produced and characterized 28 murine monoclonal antibodies to the TEM-1 plasmid-mediated ,i-lactamase. Radial immunodiffusion identified 3 monoclonal antibodies as immunoglobulin M (IgM), 18 as subclass IgGl, 2 as IgG2a, and 5 as IgG2b. Using a newly described enzyme immunoassay, cross-reactivity of 16 of these monoclonal antibodies was tested against 24 plasmid-determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Several researchers have reported that different β-lactamases may share a certain degree of homology [22,23,24]. Because several types of proteins are present in milk, it is crucial to assess any cross-reactivity in milk using the developed β-lactamase detection method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have reported that different β-lactamases may share a certain degree of homology [22,23,24]. Because several types of proteins are present in milk, it is crucial to assess any cross-reactivity in milk using the developed β-lactamase detection method.…”
Section: Resultsmentioning
confidence: 99%
“…Immunologic methods such as sandwich ELISA are effective for the detection of proteins and bacteria [18,19,20,21,22]. Suitable antibodies for the detection of β-lactamases by ELISA have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with anti-ROB-1 ␤-lactamase, anti-TEM-1 ␤-lactamase, and anti-PSE-4 ␤-lactamase antibodies have addressed in a qualitative manner the effects of point mutations on steady-state ␤-lactamase levels (10,14,25,27,30). To our knowledge, only two anti-␤-lactamase antibodies have been used in both Western blot and enzyme-linked immunosorbent assay (ELISA) formats to measure TEM-1 and PC1 ␤-lactamases (15,22).Here, we describe the production, purification, and characterization of polyclonal anti-SHV-1 and anti-CMY-2 ␤-lactamase antibodies. We chose to develop these antibodies because SHV-1 is the second most common class A ␤-lactamase found in Escherichia coli and Klebsiella pneumoniae, and CMY-2 ␤-lactamase is the most common plasmid-determined AmpC ␤-lactamase (3, 21).…”
mentioning
confidence: 99%